Sumbangsih Pendekatan Komunitas Iman Menurut Jack L. Seymour Bagi Gereja dalam Menghadapi Tantangan di Era Milenial - Upa', Febriani (Institut Agama Kristen Negeri Toraja, 2021)
The Advances in science and technology not only have a positive impact but also have a negative impact on human life. The emergence of various problems and challenges in the Millennial Era has a very impact on the lives of Christians, especially for the millennial generation. This should be a concern for churches living in the millennial era for how to make Christians have a firm faith in facing the development of science and technology in the millennial era. By utilizing the library study approach, this research shows the faith community approach according to Jack L. Seymour as a means of coaching and serving the millennial generation. This can be done by the church in helping the millennial generation in facing challenges and even problems that occur due to the development of science and technology in the millennial era.